ADUA: um nome próprio, palimpséstico e pirilâmpico - Flavia Natércia da Silva Medeiros (TRF2, 2020)
At the end of the 20th century, the installation of social inclusion devices contributed to the establishment of a crisis of mediation and political representation. Despite persistent injustices and inequalities, especially in countries whose development was based on the exploitation of enslaved people, a few signs of positive change going on can be seen. In Italy, writers like Igiaba Scego have written in Italian without forgetting their origins, giving voice to people erased from official history and stimulating a reconfiguration of Italian identity, built as white and catholic. The novel Adua, written by Scego, is told in three periods: the 1930s, marked by Benito Mussolini's fascist regime; the 1970s, when Italian pornographic industry exploited black bodies and, finally, nowadays, when thousands of Africans have died crossing the Mediterranean Sea. It also refers to the Battle of Adwa, occurred in 1896, a powerful symbol of resistance against imperialism. The name Adua is the one given to the daughter by her father when she's taken to live with him. Through the operation of this palimpsestic and fire-fly like name, I've analyzed the elaboration of traumas by Scego's fiction. Thereby we can see that this name is mostly invocated to introduce paternal sermons and paternalistic/imperialist behaviors. On the other hand, many Italians today have not heard about the historical battle. These observations lead us to think about the specificities of proper names that make many authors to consider that they do not belong to the languages besides being untranslatable.